Medicinal herbs of milk thistle, celandine and their effect on liver function - Nasirova S.Z (Genius Journals, 2024)
Since ancient times, people have called the liver the "source of life" and knew that it is the most important organ in the human body. Now scientists and doctors have a complete picture of how this gland works, what it secretes and why it can suffer. Thanks to this, we have the opportunity to maintain the liver in good condition for many decades. The liver is considered the largest gland in the human body. The main functions of the liver are metabolism, neutralization of toxins, and maintenance of metabolism. Liver cells are responsible for neutralizing toxic substances and producing bile. The liver is not called the "fat depot" for nothing - it is responsible for fat metabolism [1,2]. In addition, vitamins and hormones are metabolized in the liver. The liver breaks down poisons, toxins and substances that can cause allergies to more harmless substances. Excess vitamins in the body also pass through the liver and are broken down there. On average, in one hour this organ is able to pass through about 90 liters of blood. In economically developed countries, chronic liver diseases are among the six main causes of death in patients aged 35 to 60 years, accounting for 14-30 cases per 100,000 population. The use of medicines also negatively affects the liver, it absorbs all harmful elements like a sponge, preventing them from entering other organs with blood [3,4].
Keywords: Milk thistle; hepatitis; liver; celandine